An Unusual Presentation of Ludwig’s Angina Complicated by Cervical Necrotizing Fasciitis: A Case Report and Review of the Literature - Kristelle Chueng; David J. Clinkard; Danny Enepekides; Yousef Peerbaye; Vincent Y. W. Lin (Case Reports in Otolaryngology)
Ludwig’s angina can seldom be complicated by necrotizing fasciitis. Due to the rapidly progressing nature of this infection and the potential for airway compromise and death, it is important to be aware of different ways in which this disease process can present in order to recognize and treat it emergently. We report here an unusual presentation of a case of Ludwig’s angina complicated by necrotizing fasciitis in an elderly patient. The clinical features, diagnosis, and treatment are discussed in detail as well as a brief literature review on craniocervical necrotizing fasciitis.